Sustainable Dyeing: Utilizing Natural Ketapang Colors for Shibori Products - Widowati; Atika; Sholikhah, Roudlotus; Nurmasitah, Sita; Wahyuningsih, Sri Endah; Apriliana, Luthfiyah; Ayudianisa, Nadhifa Luthfihasna; Mutiara, Alma (Universitas Negeri Semarang, 2023)
The use of synthetic dyes in the textile industry produces wastewater with high potential for environmental pollution. Utilizing natural dyes from Ketapang leaves offers an alternative for reducing such wastewater and can be considered a sustainable dyeing method. According to data from the UNNES Conservation Development Agency, there are 5,170 Ketapang trees around the UNNES campus, indicating a plentiful supply for natural dye production. The purpose of this study is to explore the potential of Ketapang leaf dye in enhancing the aesthetic quality of Shibori products, specifically in terms of motif aesthetics and color direction. The research employs a quantitative approach with an experimental design, using a single variable. Data analysis was conducted through descriptive percentage statistics. The Shibori with the highest aesthetic value was produced using lime as a fixative, achieving a 95% rating (highly quality). Color direction analysis showed that each fixative produced different color outcomes: lime resulted in a Dijon color, alum produced a Corn color, and ferrous sulfate yielded a Seaweed color. Based on these findings, it can be concluded that natural dyes from Ketapang leaves contribute significantly to both motif aesthetics and color direction in Shibori dyeing, offering a sustainable and environmentally friendly alternative for textile production.